EVALUASI HASIL BELAJAR PENDIDIKAN ISLAM DI MADRASAH DAN PONDOK PESANTREN - Rini Nopita; Decky Saputra (LPPM STAI Muhammadiyah Probolinggo, 2025)
The purpose of this study is to evaluate the results of Islamic education in madrasahs and pesantren. The significance of comprehending the distinctions between the two institutions' methods in accomplishing the objectives of Islamic education forms the basis of the study's background. Descriptive qualitative research methodology is employed, and literature reviews are done to gather data. The study's findings demonstrate notable variations in curriculum, instructional strategies, and assessment practices. Pesantren places a strong emphasis on students' character and spiritual growth via habituation in everyday life and a holistic approach. The formal education system used in madrasahs, on the other hand, is centered on the mastery of structured academic understanding and cognitive knowledge. Every strategy has pros and cons when it comes to producing graduates who are obedient, informed, and morally upright. The study's conclusions confirm that both establishments are strategically important to Indonesia's growth in Islamic education. To develop a more contemporary, integrative, and contextual Islamic education methodology, a thorough grasp of each is required.